Uranium, Thorium and Protactinium isotopes of ODP Site 172-1063, supplementary data to: Lippold, Jörg; Gruetzner, Jens; Winter, Diane M; Lahaye, Yann; Mangini, Augusto; Christl, Marcus (2009): Does sedimentary 231Pa/230Th from the Bermuda Rise monitor past Atlantic Meridional Overtuning Circulation?. Geophysical Research Letters, 36, L12601 - Lippold, Jörg; Gruetzner, Jens; Winter, Diane M (PANGAEA - Data Publisher for Earth & Environmental Science, 2009)
Ocean circulation may have undergone reductions and reinvigorations in the past closely tied to regional climate changes. Measurements of 231Pa/230Th ratios in a sediment core from the Bermuda Rise have been interpreted as evidence that the Atlantic Meridional Overturning Circulation (AMOC) was weakened or completely eliminated during a period of catastrophic iceberg discharges (Heinrich-Event 1, H1). Here we present new data from the Bermuda Rise that show further 231Pa/230Th peaks during Heinrich-2 (H2) and Heinrich-3 (H3). Additionally, a tight correlation between diatom abundances (biogenic silica) and 231Pa/230Th is discovered in this core. Our results redirect the interpretation of 231Pa/230Th from the Bermuda Rise as a proxy for ocean circulation towards a proxy that reacts highly sensitive to changes of particle composition and water mass properties.